ADR practice in planning conflicts: Australian lawyers' thinking on ADR, training and mentorship. Issue 2 (4th May 2022) - Douglas, Kathy; Goodman, Robin; Kallies, Anne
ABSTRACT: Lawyers' alternative dispute resolution (ADR) practice is an important part of legal practice and education. In this research project, we explored the views of planning lawyers in Melbourne, Australia who were engaged in the ADR processes of mediation and compulsory conferencing. The participants interviewed endorsed the use of ADR in planning disputes and spoke of the need to adopt a collaborative approach drawing on their negotiation and communication skills. They also spoke of their role providing legal expertise in a complex jurisdiction. The lawyers reflected on the nature of planning disputes where conflict can be emotional as disputes deal with the communities' lived experience of the built environment and the wider concerns of the planning of cities. The lawyers showed the ability to focus on the larger justice issues that affect the jurisdiction. Additionally, the study explored the lawyers' views on their training in ADR. While some participants appreciated ADR training courses, many pointed to the benefits of learning from those lawyers experienced in planning law disputes. The research presented here suggests the need for ongoing peer support and mentorship for lawyers in the use of ADR, in addition to training, that is particular to their jurisdiction.